2019
DOI: 10.1039/c8cp06412a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and quantum yields of H2 + CH2CO as a primary photolysis channel in CH3CHO

Abstract: A new ketene + H2 channel in CH3CHO photolysis is not modelled by quasi-classical trajectories over the transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Harrison et al also revealed ketene as a major product in photolysis experiments conducted at 305.6 nm and confirmed that this molecule forms alongside molecular hydrogen from acetaldehyde molecules. [57] In the solid phase, only limited studies were conducted. [58] On the other hand, electron spin resonance (ESR) studies of solid acetaldehyde in noble gas matrices at 77 K exposed to high energy electrons (1 MeV) revealed acetyl (CH3ĊO) to be the dominating radical.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison et al also revealed ketene as a major product in photolysis experiments conducted at 305.6 nm and confirmed that this molecule forms alongside molecular hydrogen from acetaldehyde molecules. [57] In the solid phase, only limited studies were conducted. [58] On the other hand, electron spin resonance (ESR) studies of solid acetaldehyde in noble gas matrices at 77 K exposed to high energy electrons (1 MeV) revealed acetyl (CH3ĊO) to be the dominating radical.…”
Section: Introductionmentioning
confidence: 99%
“…There has been recent interest in the formation of ketenes as atypical and relatively uncharacterised products of carbonyl photolysis (Harrison et al, 2019;Toulson et al, 2018). As seen above, the formyl + α H 2 -loss mechanism forms ketenes in aldehydes and the AE mechanism forms ketenes in ketones.…”
Section: Enal-ketene Tautomerisationmentioning
confidence: 99%
“…7 reinforce, for multiple carbonyl species, that only H 2 -loss from the formyl and α positions is energetically accessible in the actinic energy range. Indeed, the 4-centre H 2 -loss channel in acetaldehyde has recently been observed experimentally under tropospherically relevant conditions (Harrison et al, 2019). In the absence of a formyl hydrogen, none of the ketone H 2 -loss channels are accessible in the troposphere.…”
mentioning
confidence: 98%
“…The most apparent difference in the photochemistry of these molecules is in the minor pathway producing CH 2 CO + H 2 in CH 3 CHO [20]. The transition state for the analogous pathway in CF 3 CHO could not be located; instead a hydrogen-bonding interaction is formed between the formyl H-atom and a fluoromethyl fluorine atom leading to CF 2 , HF and CO products.…”
Section: Photodissociation Pathwaysmentioning
confidence: 99%